Co-representation breaks down beyond the dyad in UK adults - Sophie J. Milward; Jamie Whitehouse (PLoS ONE, 2025)
Cooperation is so deeply embedded in human psychology that we spontaneously track a partner’s task as well as our own when acting in a pair. This automatic ‘co-representation’ of a partner’s mental representation of their task has been argued to be key to the sophisticated social coordination we see in human adults. However, our day-to-day encounters are not limited to one-to-one interactions. This is the first published study to investigate co-representation in groups, with results from a group Joint Simon task suggesting that co-representation may break down in groups larger than two. Exploratory analyses also suggested a complex interplay between spatial and social relationships between individual members within a group. We propose a novel hypothesis based on these findings: when we lack the capacity to track everyone in a group, we may be able to selectively track those who are the most salient or relevant. This provides key information about the limits of our capacity to keep others in mind, and the psychological underpinnings of how we do so.